MARKET ANOMALY ANALYSIS: THE DAY OF THE WEEK EFFECT, JANUARY EFFECT, ROGALSKY EFFECT AND WEEKFOUR EFFECT TESTING IN INDONESIA STOCK EXCHANGE (CASE STUDY ON COMPANIES LISTED IN LQ45 INDEX IN 2013- 2017) - Wendra Bagaskara; Khairunnisa Khairunnisa (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2019)
Financial theory explained that there are four types of anomalies such as firm anomaly, seasonal anomaly, event anomaly, and accounting anomaly. Seasonal anomalies are divided into several parts such as The Day of The Week Effect, the January Effect, Rogalsky Effect, and Week-Four Effect. The results of research in Indonesia show mixed results related to this anomaly.The purpose of this research is to test wether The Day of The Week Effect, January Effect, Rogalsky Effect, and Week-Four Effec market anomalyt occurred on the Indonesia Stock Exchange. This research is a study that uses quantitative research methods with the purpose of descriptive-verification. The unit of analysis of this research is the companies that registered consistently in the LQ45 index for the period 2013-2017 using purposive sampling technique. This study used 37 research samples for 5 years of research and used a different test analysis with SPSS Statistics 25.The results showed that there was an anomaly of The Day of The Week Effect on the Indonesia Stock Exchange and there was no anomaly in the January Effect, Rogalsky Effect, and Week-Four Effect on the Indonesia Stock Exchange